Almighty : Courage, Resistance, and Existential Peril in the Nuclear Age - Zak, Dan (New York Blue Rider Press, 2016)
"A riveting, chilling tale of how a group of ragtag activists infiltrated one of the most secure nuclear weapons sites in the United States, told alongside a broader history of America's nuclear stewardship, from the early stages of the Manhattan Project to our country's never-ending investment in nuclear weaponry. On Saturday, July 28, 2012, three senior citizens broke into one of the most secure nuclear weapons facilities in the world. An eighty-two-year-old Catholic nun, a Vietnam veteran, and a house painter infiltrated the Oak Ridge, Tennessee, complex in the dead of night, smearing the walls with human blood and spray-painting quotes from the Bible. Then they waited to be arrested. What was a simple plan--one far more successful than even its perpetrators expected -- spawned a complex discussion. Among the questions that the infiltration raised: How did three unarmed civilians manage to penetrate one of the most heavily guarded locations in the world, nicknamed the 'Fort Knox of Uranium'? Why does the United States continue to possess more nuclear weaponry than is needed to destroy global civilization many times over? And what does this mean for the day-to-day safety of Americans? In Almighty, Washington Post writer Dan Zak begins with the present-day axis of a seventy-year-old story, exploring how events of the twentieth century -- including the prophecies of a farmer-turned-ascetic named John Hendrix and the early stages of the Manhattan Project in Morningside Heights -- led to one of the most successful and high-profile demonstrations of anti-nuclear activism"--Amazon.com.
Include Illustrations, Notes, Bibliography and Index
Keywords: Military policy -- Nuclear weapons -- Nuclear weapons industry